2000
DOI: 10.1080/713755916
|View full text |Cite
|
Sign up to set email alerts
|

Visual Similarity Effects in Immediate Verbal Serial Recall

Abstract: The role of visual working memory in temporary serial retention of verbal information was examined in four experiments on immediate serial recall of words that varied in visual similarity and letters that varied in the visual consistency between upper and lower case. Experiments 1 and 2 involved words that were either visually similar (e.g. fly, cry, dry; hew, new, few) or were visually distinct (e.g. guy, sigh, lie; who, blue, ewe). Experiments 3 and 4 involved serial recall of both letter and case from seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
145
3
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(169 citation statements)
references
References 52 publications
15
145
3
5
Order By: Relevance
“…It theoretically could be a visuospatial form of rehearsal. Logie, Della Sala, and Wynn (2000) found that visual codes play a role in verbal recall. However, they used visual stimuli whereas Morey and Cowan used spoken stimuli for the digit load.…”
Section: Running Memory Spanmentioning
confidence: 99%
“…It theoretically could be a visuospatial form of rehearsal. Logie, Della Sala, and Wynn (2000) found that visual codes play a role in verbal recall. However, they used visual stimuli whereas Morey and Cowan used spoken stimuli for the digit load.…”
Section: Running Memory Spanmentioning
confidence: 99%
“…Baddeley"s (2000) revised working memory model adds the possibility that relevant long-term knowledge might facilitate encoding and/or retrieval when it is combined with the verbal memory trace in the episodic buffer. The current data are compatible with this revised model Our interpretation is that the higher performance in the keypad condition was caused by integration of long-term knowledge about the very familiar telephone keypad.…”
Section: Keypad Displaymentioning
confidence: 99%
“…However, experimental results suggest that such separation is not absolute : Baddeley, Lewis and Vallar (1984) observed that when concurrent articulation was employed to prevent the use of the phonological loop, participants" recall of visually presented digits was reduced, but not eliminated. Logie, Della Sala, Wynn and Baddeley (2000) demonstrated visual similarity effects on a verbal serial recall task. The "episodic buffer" (Baddeley, 2000) is a proposed secondary memory store that was developed in part to help understand these patterns.…”
mentioning
confidence: 99%
“…This is attributed to interference caused in the memory trace when trying to store and retrieve items with similar visual characteristics (e.g. Frick, 1988a;1988b;Hitch, Halliday, Schaafstal, & Schraagen, 1988; Coding strategies in picture memory span 8 Logie, Della Sala, Wynn & Baddeley, 2000). Visual coding has often been reported in samples of fiveyear-olds but not in older children (Brown, 1977;Hayes & Schulze, 1977;Hitch et al, 1988;Hitch, Woodin & Baker, 1989;Hitch et al, 1991;Longoni & Scalisi, 1994;Palmer, 2000a).…”
mentioning
confidence: 99%